Pengaruh Sistem Cross Check 5 Right Terhadap Kejadian Exposure Breast Milk (EBM ) - Hanna Harnida (2018)
Mom’s Breast Milk is the main nutrition for baby, which determines the baby’s growth and development if the breast milk is enough and sufficiently given to the baby. Nevertheless, if there is separate treatment between mom and the baby happens, it could occurs some mistakes in giving the breast milk or Exposure Breast Milk. Cross Check 5 Right System is one of the way to prevent or reduce the chance of Exposure Breast Milk. The aim of this research is to know how far the effect of Cross Check 5 Right System towards Exposure Breast Milk. The research’s design is using Cross Sectional with total sample of 30 respondents. The population is using 0-1 month old baby patients in NICU Premier Surabaya Hospital which meets the inclusion criteria. The Variable Independent is Cross Check 5 Right System and the Variable Dependent is Exposure Breast Milk (EBM). The data collecting for observation is implementing the Cross Check 5 Right System in giving the baby breast milk during 4 weeks. The data is analyzed by Chi-Square statistic test with level of p < 0,05. The result using Chi-Square test is shown by p = 0,001 Cross Check 5 Right System. So, it can be concluded that there is a correlation between Cross Check 5 Right System towards the Exposure Breast Milk (EBM) in Neonatus Intensive Care (NICU) in Premier Surabaya Hospital.The conclusion is Cross Check 5 Right System has been proven that it can prevent and reduce the Exposure Breast Milk (EBM) in NICU Premier Surabaya Hospital.